Konflik peran kerja-keluarga pada ibu bekerja terhadap perilaku obesogenis anak sekolah dasar - Almira Sitasari; Madarina Julia; Toto Sudargo (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: Childbearing pattern of parents greatly affects the healthy lifestyle of children including behaviors preventing children from obesity. Working mothers with a dual role at work and the family face challenges in doing so.Objective: To identify the effect of work-family conflict in working mothers to obesogenic behaviors of elementary school children at Yogyakarta Municipality.Method: This was a quantitative study with cross sectional design. Obesogenic behaviors were assessed using questionnaire of Family Health Behavior Scale. Role conflict was assessed using questionnaire of Work-Family Conflict filled by working mothers. Nutrition status of children was assessed using a parameter of body mass index by age with the standard of WHO 2007.Results: The result of the study showed 47.73% of working mothers had high role conflict and 45.26% of children had high obesogenic behaviors. There was no effect of work-family conflict in working mothers to obesogenic behaviors of elementary school children at Yogyakarta. The influencing factors were family income (p<0.001); position/job type (p<0.001); gender (p<0.05); and nutrition status (p<0.05).Conclusion: Work-family conflict in working mothers had no effect to obesogenic behaviors of elementary school children at Yogyakarta Municipality.